Factors Influencing Self-Development of Nurses at Sing Buri Hospital - Surichamorn, Suwan (Journal of Health Science of Thailand, 2019)
Self-development is very crucial for nurses because nursing services need to change and adapt according to the context of policy, technology, and society. Thus, nurses need to have ability, skills, and self-development in respond to those changes. The objectives of this descriptive research and analytical were : (1) to explore self-development of nurses, (2) to investigate the relationship between the personal data and self-development of nurses, and (3) to study factors influencing self-development of nurses at Sing Buri hospital. All nurses at the hospital (328 ) were the population of this study. The research instruments were questionnaires, verified for content validity and tested for reliability. The Cronbachีs alpha reliability coefficient was 0.86. Data were analyzed by descriptive statistics (including frequency, percent, mean,and standard deviation), Pearson correlation coefficient, and stepwise multiple regression analysis. It was found that most nurses were 41-50 years old and earned bachelor degrees. Most were married and having 10-20 year of working experiences. The nurses as a whole, rated their self-development as high yet those with 1-10 year and 31-40 year experiences rated their self-development at a medium level. Whereas nurses who had 11-20 year and 21-30 year experiences rated their self-development at a high level. There was no correlation between age nor marriage status with their self-development. There was very low correlation between experience of nurses and their self-development (p-value 0.05). Lastly, experience of nurse influenced their self-development, and the predicting power was 16 percent (R2 = 0.16 )